Pengaruh Edukasi Kelas Ibu Hamil Terhadap Kemampuan Dalam Deteksi Dini Komplikasi Kehamilan - Winarsih, Wiwin; Wulandari, Setyo Retno (Madu : Jurnal Kesehatan, 2024)
Every pregnancy has a risk of complications that can threaten the lives of the mother and baby. Risks that can occur in pregnancy include being too young to get pregnant, too old to get pregnant > 35 years, too close or far apart pregnancies and too many children or often known as 4 Too. One effort that can be made to prevent pregnancy complications in pregnant women is to increase the mother's knowledge about early detection of pregnancy complications through education in pregnancy classes. Through education in pregnancy classes, it is hoped that pregnant women can have the ability to detect complications early during pregnancy so that they can reduce maternal and fetal mortality rates. Objective of this study to determine the effect of education in pregnancy classes on the ability to detect early pregnancy complications. This study is a quantitative study with a pre-experimental design with a one group pretest and posttest design. The population in this study was 321 people. The sampling technique used was purposive sampling of 77 people. The results of statistical analysis using Wilcoxon test that had been carried out obtained a p value of 0.000, because the value of 0.000 <0.05, the hypothesis in the study was accepted. Conclusion: There is an influence of education for pregnant women's classes on the ability to detect early pregnancy complications in the Kalasan Health Center Work Area in 2024.